Cookies of Bamboo Shoots as Functional Food - Rika Wulandari (Biopropal Industri, 2010)
The research of cookies of bamboo shoots was as functional food carried out to increase the utilization of bamboo shoots that were very potential in West Kalimantan as functional food. The bamboo soot cookies was made from dry processing of luxuriant bamboo shoots to mamboo shoots flour, and the production of bamboo shoots cookies. Results of analysis showed luxuriant bamboo shoots contained thewater 94.4 %, ash 0.28 %, protein 1.6 % fat 4.78%, carbohydrate 0.637 %, rough fibre 2.03%, vitamin C 0,003 %, phosphor 0.120 %, calcium 114 mg/kg, and sodium 27,4 mg/kg. Dry bamboo shoots were produced through the process bleaching with the solution to salt 3% and produced bamboo shoots flour with results efficiency 6,25 % and had the content of the level of water 5,66%, the level of ash 6,44 %, protein 20.9 %, fat 3.64 %, the carbohydrate 17.9 %, rough fibre 3.97%, and vitamin C 0.0021 %. Best bamboo shoots cookies that is to the C treatment variable that was produced from the mixture of bamboo shoots flour: wheat flour: maize flour = 20:60:20. Results of the analysis were based on the standard of the quality of the biscuit (SNI-0-2973-1992) showed that the product that was produced contained the water 4,14%, ash 3.22%, protein 8.95%, fat 16.5%, carbohydrate 37,01%, rough fibre 0.379%, calorie 332,34 cal, and the Executive Board’s metal < 0,040 mg/kg, Cu 1,92 mg/kg, Hg<0,004 mg/kg, as well as Zn 27,1 mg/kg. Bamboo shoots cookies that were produced were categorised as functional food that could help the process of the digestion so as to be estimated could reduce the risk of colon cancer.